Perhitungan Waktu pada Proses Skematik Desain Arsitektur Parametrik Bangunan Sekolah Terbuka (Studi Kasus: Green School Bali) dengan Material Utama Bambu - Heru Prasetiyo Utomo; I Gusti Agung Ayu Berliana Firly Mahendra (Universitas Medan Area, 2026)
Education in the millennial generation is very developed and diverse. One of them is interactive learning about nature also hones their concern for the natural flora and fauna as well. The Green School Bali school building is one of the potential large-scale buildings with bamboo architecture that is renewable, elastic and not easy to break. In this study, the researcher wanted to explore the effectiveness of the bamboo design with a parametric design method. This research uses qualitative methods with literature studies and design simulations. Rhinoceros and grasshopper are used as a study tool to implement the parameters of the building's parametric design. The results of the study are expected to show the speed and efficiency of this application so that it can get an overview of the design process in the future.